6a+12=2a+-16

Simple and best practice solution for 6a+12=2a+-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a+12=2a+-16 equation:


Simplifying
6a + 12 = 2a + -16

Reorder the terms:
12 + 6a = 2a + -16

Reorder the terms:
12 + 6a = -16 + 2a

Solving
12 + 6a = -16 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
12 + 6a + -2a = -16 + 2a + -2a

Combine like terms: 6a + -2a = 4a
12 + 4a = -16 + 2a + -2a

Combine like terms: 2a + -2a = 0
12 + 4a = -16 + 0
12 + 4a = -16

Add '-12' to each side of the equation.
12 + -12 + 4a = -16 + -12

Combine like terms: 12 + -12 = 0
0 + 4a = -16 + -12
4a = -16 + -12

Combine like terms: -16 + -12 = -28
4a = -28

Divide each side by '4'.
a = -7

Simplifying
a = -7

See similar equations:

| -4(7)+2(-9)-7(-9)=z | | 3*4/5 | | (x-4)(x^2-7x+2)= | | m+3m+4m+4= | | 2/6*3/4 | | 44-5h=6h | | X=20+-0.4y+-0.02z | | 9x-3(x-8)=6(x-3)+6 | | 20000(.06x+.07y)=1300 | | 9x-3(x-8)=6x-24 | | 13q-2=-28 | | 6-2x=4(2-3x)+8x | | 9=-2m+-1 | | .93x+.97(4-x)=3.8 | | 2(x-4)-x=3 | | (3x-3)(3x-8)= | | 1+8(-4n-2)=-39-8n | | -2/3r+2r=6/5r+12/5 | | (4x^2+1)(6x^2+7)= | | 5x-6-2x=4x+8 | | 6x+6=6x-9 | | 2/3(6x+9)=18 | | -8v=-80 | | -2(-x-8)=2x+15 | | -3(x-5)+12x=9(x+2)+12 | | 60+15=4 | | d-16=-50 | | 2(6w+8)=2(4w+24) | | (3x+5)=2(x+7) | | -6(x-8)=48 | | n+t+g+h=106 | | 162=11x+19 |

Equations solver categories